2020
DOI: 10.3390/v12050489
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HIV Markers between Infected Individuals Treated with Different ART Regimens: Implications for the Persistence of Viral Reservoirs

Abstract: In adherent individuals, antiretroviral therapy (ART) suppresses HIV replication, restores immune function, and prevents the development of AIDS. However, ART is not curative and has to be followed lifelong. Persistence of viral reservoirs forms the major obstacle to an HIV cure. HIV latent reservoirs persist primarily by cell longevity and proliferation, but replenishment by residual virus replication despite ART has been proposed as another potential mechanism of HIV persistence. It is a matter of debate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 165 publications
(187 reference statements)
2
11
0
Order By: Relevance
“…On average, CA RNA levels were 1.75-2-fold lower in the NNRTI-treated participants. This confirms numerous reports that measured lower residual plasma viremia in NNRTI-compared to PI-treated individuals [28]. In fact, also in this study low-level plasma HIV RNA was more frequently detectable in PI-treated than in NNRTI-treated participants, despite no difference in therapy adherence by regimen.…”
Section: Discussionsupporting
confidence: 91%
“…On average, CA RNA levels were 1.75-2-fold lower in the NNRTI-treated participants. This confirms numerous reports that measured lower residual plasma viremia in NNRTI-compared to PI-treated individuals [28]. In fact, also in this study low-level plasma HIV RNA was more frequently detectable in PI-treated than in NNRTI-treated participants, despite no difference in therapy adherence by regimen.…”
Section: Discussionsupporting
confidence: 91%
“…On average, CA RNA levels were 1.75-2-fold lower in the NNRTI-treated participants. This confirms numerous reports that measured lower residual plasma viremia in NNRTI-compared to PI-treated individuals [28].…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, finding such a difference would suggest that some regimens are more potent in suppressing residual replication than others, arguing that virus suppression is less complete with at least some of the regimens. A number of studies reported lower levels of residual viremia in individuals treated with NNRTI-based, compared to PI-based, ART regimens ( [26,27], reviewed in [28]). However, to date, few studies have compared levels of CA HIV reservoir markers between different ART regimens [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Author details 1 Department of Internal Medicine, Infectious and Tropical Diseases, University Clinics of Kinshasa, Kinshasa, Democratic Republic of the Congo. 2 Biostatistics and Medico-economic Information Department, University Hospital of Liege, Liège, Belgium. 3 Department of Internal Medicine and Infectious Diseases, Liège University Hospital, Liège, Belgium.…”
Section: Fundingmentioning
confidence: 99%
“…Antiretroviral therapy (ART) represents a remarkable success in recent medicine. ART radically decreases the morbidity and mortality of human immunodeficiency virus (HIV)-infected individuals and drastically reduces the risk of HIV transmission [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%